Delayed-onset facial nerve paresis following cochlear implantation: case report and literature review. Issue 12 (19th December 2018) - Lawrence, R; Jeffs, E; Hartley, DEH
Abstract: Objective: Facial nerve paresis is rare following cochlear implantation. Mechanisms underlying delayed-onset facial paresis are poorly understood. This paper describes the case of a patient who developed facial nerve paresis three years after implantation. A literature review was performed with the aim of identifying any similar cases. Methods: The patient case is reported, and the literature reviewed using PubMed, Embase and Ovid databases. Results: The literature review revealed that the vast majority of delayed-onset facial nerve paresis cases occur within the first month of implantation. Only two other cases occurring years after device implantation were identified. Although potential causative factors have been suggested, as in our case this phenomenon may be idiopathic. Conclusion: Prognosis for recovery of late-onset facial nerve paresis seems promising, despite the unfortunate requirement for device explantation in all previous cases including our own.